High prevalence of prescription of psychotropic drugs for older patients in a general hospital - Inken Arnold; Kati Straube; Wolfgang Himmel; Stephanie Heinemann; Vivien Weiss; Laura Heyden; Eva Hummers-Pradier; Roland Nau (BMC, 2017)
Abstract Background Many elderly patients receive psychotropic drugs. Treatment with psychotropic agents is associated with serious side effects including an increased risk of falls and fractures. Several psychotropic drugs are considered potentially inappropriate for treatment of the elderly. Methods A retrospective chart review was conducted covering all patients aged ≥ 65 years who were admitted to Evangelisches Krankenhaus Göttingen-Weende between 01/01/2013 and 03/31/2013. Psychotropic drugs reviewed for included benzodiazepines, Z-drugs, antidepressants and neuroleptics, but not drugs for sedation during artificial ventilation or pre-medication before surgery. Potentially inappropriate drugs were identified according to the PRISCUS list. To assess which factors were associated with the administration of psychotropic drugs, univariate and multivariable logistic regression analyses were performed. Results The charts of 2130 patients (1231 women) were analyzed. 53.9% of all patients received at least one psychotropic medication (29.5% benzodiazepines, 12.6% Z-drugs, 22.2% antidepressants, 11.9% neuroleptics). The mean number of psychotropic drugs prescribed per patient with at least one prescription was 1.6. Patients treated in the geriatric department most often received antidepressants (45.0%), neuroleptics (20.6%) and Z-drugs (27.5%). Benzodiazepines and Z-drugs were prescribed mostly as medication on demand (77.7% of benzodiazepines, 73.9% of Z-drugs). Surgical patients most frequently received benzodiazepines (37.1%). Nearly one-third of all patients ≥ 65 years was treated with at least one potentially inappropriate psychotropic medication. The mean number of potentially inappropriate psychotropic medications per patient with at least one psychotropic prescription was 0.69. The percentage of patients with potentially inappropriate psychotropic medication was highest in the surgical departments (74.1%). Female gender (adjusted OR 1.36; 95% CI 1.14 to 1.63), stay in the Department of Geriatrics (2.69; 2.01 to 3.60) or the interdisciplinary intensive care unit (1.87; 1.33 to 2.64) and age ≥ 85 years (1.33; 1.10 to 1.60) were associated with psychotropic drug treatment. Conclusions A high percentage of patients aged ≥ 65 years received psychotropic drugs. The chance that a potentially inappropriate psychotropic drug would be administered was highest in the surgical departments. Antidepressants, neuroleptics and Z-drugs were used surprisingly often in geriatric medicine. Educational strategies could reduce the use of psychotropic drugs and the prescription of potentially inappropriate medications.